Комп’ютеризована система обробки та аналізу цифрових зображень, отриманих при електронно-променевому зварюванні - Івасенко, І.Б.; Журавель, І.М.; Сущик, К.В.; Берегуляк, О.Р. (Інститут програмних систем НАН України, 2008)
The problem of determination of junction lines of objects on images gained at electron-beam welding is considered. Image contrast enhancement is performed by three-stage method based on fuzzy logic. For the determination of welding trajectory locally adaptive approach to segmentation of junction lines of objects and tracing of their contours based on the analysis of image brightness characteristics changes are proposed. Joint сurve is represented analytically with optimal parametrical spline approximation using LSM approximation on each spline link.